The effects of music therapy on the pain response of premature neonates after venipuncture - Gacias-Ocampo, Leslie
The use of music therapy for the care of the premature neonates is relatively new and not much is known about its beneficial effects in minimizing the pain response experienced by neonates undergoing medical treatment. Recent studies, however, reveal associations between the use of music therapy and improved oxygenation, increased weight gain, decreased hospital stay and improved behavioral state among neonate infants. The present study attempted to determine the effectiveness of music therapy in modulating the pain response of neonates in terms of improved oxygenation, decreased heart rate acceleration, and lower pain scores. This study was a double-blind experimental design with randomization. A total of 40 premature neonates were included in the study; each was randomly assigned to either the experimental or the control group. The experimental group was exposed to classical instrumental music while the control group was exposed to pre-recorded background noise that simulated actual environmental sounds. The intervention delivered via headphones was initiated 30 minutes before a scheduled venipuncture and terminated 5 minutes after the procedure. The tool used was a modified version of the Premature Infant Pain Profie (PAT) referred to in the study as the Pain Assessment Tool. It was modified by the clinical investigator to suit the needs of the study. It is a pain scale that incorporates both physiologic (heart rate and oxygen satuation) and behavioral indicators of pain (facial expressions).
Factors that modify pain responses in neonates such as behavior state and age of gestation were also incorporated in the tool. Independent t test was utilized to determine comparability of subjects in terms of clinical profile, and baseline values of heart rate, oxygen saturation and pain scores. Chi square analysis was used to determine comparability of the two groups in terms of distribution of male and female subjects. Results showed that there was no significant difference between the two groups in terms of birht weight (p value+0.196), age of gestation (p value=0.545), post natal age (p value=0.137) and in scores obtained at the Physiologic Stability Index (p value=0.185). There was also no significant differences in baseline values for oxygen saturation (p value=0.235), heart rate (p value=0.376), and pain scores (p value=0.555). There was also no significant difference between the unequal distribution of male and female subjects on each group (p value=0.119). Repeated Measures Analysis of Variance was used to analyze the post test data. Findings include the following. Results showed that the experimental group had lower heart rate readings from Observation 1 to Observation 3 as compared to the control group. But this finding was statistically not significant (p value=0.412). In terms of oxygen saturation, results showed that the experimental group had higher oxygen saturation levels from Observation 1 to Observation 3 as compared to the control group, but this was not statistically significant (p value=0.099). This study was also found out that all subjects on both groups exhibited behavioral indicators of pain with difference in duration. The study also showed that music therapy significantly reduced the pain scores of subjects in the experimental group (p value=0.04). Interpretation of their pain scores that the experimental group had minimal pain as compared to the group who experienced moderate to severe pain at Observation 1. This study concluded that music therapy can be an effective intervention for neonates which nursed can utilize to minimize procedural pain in premature infants. Although the less acceleration in heart rate and higher oxygen saturation experienced by the experimental group in response to pain is not statistically significant, it may still be of clinical value to clinicians. This study also concluded that the use of behavioral indicators on their own doen not provide a good picture of the degree of pain among neonates, especially when utilizing the Premature Infant Pain Profile, it should be used in conjuction with the physiologic indicators. It is recommended that this study be replicated among premature neonates admitted for more that 7 days and thos on oxygen therapy. Considerations should also be taken in controlling for the effects of gender in tolerance to music intervention, as previous studies have shown that female neonates benefit more from music therapy. In terms of nursing practice, it is recommended that a feasibility study be done on the applicability of providing music therapy in the local setting, as well as the cost-effectiveness of using music therapy over the use of analgesia in alleviating pain experienced by neonates.
Thesis (MA in Nursing)--University of the Philippines Manila.
Keywords: Music therapy; Infants (Premature), Effects of music on